Value and obligation - "Brandt, Richard B." (New York, 1961)
Most people interested in the problems of ethics aspire to two kinds of knowledge, one systematic, the other historical. They wish a systematic understanding of the field: knowledge of what are the various problems and their interrelations and knowledge of what has been done toward the solution of these problems. They also wish to learn what the great historical philosophers -- particularly those who have had the most important ideas about values and conduct -- have said about the subject. This book is intended to enable the reader to approximate the achievement of these twin goals at once.
Keywords: Value